No-feedback rate control algorithm for Wyner-Ziv video coding - SONG Bin; YANG Ming-ming; QIN Hao; HE Hong (Tongxin xuebao)
To avoid using feedback channel,an encoder rate control algorithm for Wyner-Ziv video coding was proposed.Firstly,using the target frame-rate and the target bit-rate,It could determine the bit allocation for each group-of-picture（GOP）.According to the correlation between adjacent frames,the bit budget for a GOP were further allocated to key frame and Wyner-Ziv frames within the GOP by dynamically choosing quantization parameter and quantization matrices.Then,with refinement of correlation-noise model（CNM） parameter,different LDPC（low-density parity-check） check matrices might be chosen for each bitplane to control the encoding bitrate of Wyner-Ziv frame.Experimental results show that the difference between expected target bitrate and actual encoded bitrate is less than 0.57% using the proposed method,and compared with existing algorithm,average PSNR（peak signal-to-noise ratio） of decoded video quality can be increased by 1 dB.In addition,our algorithm slightly increases encoder complexity,and can be used in practice.